Street world : urban art and culture from five continents - Gastman, Roger; Neelon, Caleb; Smyrski, Anthony; Harry N. Abrams, Inc. (New York : Abrams, 2007)
Urban subcultures have joined together to become something larger, more powerful, and more pervasive than ever before. Our new global urban culture, street culture at its broadest, is its force. The more than 1,000 photographs featured here together form a journey, a record, and an inspiration. The world's streets are its most vibrant sites of visual creativity, and amid their crush are photographers, documenting, creating, and collectively bringing this book to you. Their stories are the stories of the interconnectedness of global street culture. Travel and exploration are near the essence of street cultures, and the travelers who have used their passions to cross the boundaries of nations are at the heart of the process of cultural exchange.--[from publisher's description]
Looking good Getting around -- Getting up Inspiration Coming together
Keywords: Street life; Street art; City and town life; Streets -- Social aspects; Counterculture